2022
DOI: 10.1097/md.0000000000029470
|View full text |Cite
|
Sign up to set email alerts
|

Advances in neuroRehabilitation of TREM2-related dementia

Abstract: Rationable:The aim of this study is to investigate the effects of an advanced neuroRehabilitation protocol using virtual reality in the treatment of a patient with fronto-temporal dementia due to TREM2 mutation.Patient's concern: A 41-year-old caucasian male, affected by Nasu-Hakola Disease (NHD), presented a 1-year history of change in behavioral and cognitive functioning, before our observation. The onset of the disease was characterized by severe pain in the lower limbs and knees with limitations in the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…Regarding case reports, no improvement in cognitive impairment (as indicated by a reliable change index equal to 1.3) after two months of VRRS based cognitive training was observed in an adult patient with neurocognitive and motor dysfunctions due to brain alterations linked to brain-stem radionecrosis (Tartamella et al, 2020). Similarly, no improvement in global cognition and executive functions was observed in a patient with neurodegenerative disease after VRRS training (De Luca et al, 2022a). Maresca et al (2018) reported improvement in general cognitive status, attention process and prefrontal cortex related executive functioning of a patient with spinal cord injury that underwent combined treatment including both standard treatment (i.e., psychological counselling, standard cognitive training, and physiotherapy) and VRRS cognitive training.…”
Section: Non-experimental Designmentioning
confidence: 95%
See 1 more Smart Citation
“…Regarding case reports, no improvement in cognitive impairment (as indicated by a reliable change index equal to 1.3) after two months of VRRS based cognitive training was observed in an adult patient with neurocognitive and motor dysfunctions due to brain alterations linked to brain-stem radionecrosis (Tartamella et al, 2020). Similarly, no improvement in global cognition and executive functions was observed in a patient with neurodegenerative disease after VRRS training (De Luca et al, 2022a). Maresca et al (2018) reported improvement in general cognitive status, attention process and prefrontal cortex related executive functioning of a patient with spinal cord injury that underwent combined treatment including both standard treatment (i.e., psychological counselling, standard cognitive training, and physiotherapy) and VRRS cognitive training.…”
Section: Non-experimental Designmentioning
confidence: 95%
“…physiotherapy and occupational therapy), roboticaided training, and sessions of neuromotor training based on VRRS, could provide more advantages than conventional treatment alone in improving motor functions. De Luca et al (2022a) reported an improvement in head and trunk control in a patient with Nasu-Hakola disease (i.e., a rare neurodegenerative disorder) after a multimodal treatment including both VRRS and standard physiotherapy.…”
Section: Nonexperimental Designmentioning
confidence: 99%
“…The empirical evidence supporting the use of VR in cognitive rehabilitation has been steadily growing, highlighting its potential to enhance cognitive functions and quality of life for individuals with various neurological conditions [6,[108][109][110][111]. Numerous studies have demonstrated the effectiveness of VR interventions in improving well-being [4,112,113], symptoms of depression, apathy, anxiety, and agitation [45,112,114,115], perceived stress [116], global cognition, and specific cognitive domains such as attention, memory, executive functions (EFs), and spatial awareness [6,110,116].…”
Section: The General Impact Of Vr Interventionsmentioning
confidence: 99%
“…Indeed, SABI motor and cognitive therapy should be as intensive and long lasting as possible to allow patients to achieve the best independence and QoL [7]. Notably, neurorehabilitation approaches may be classified into 2 main categories: conventional, using paper-and-pencil exercises (for cognitive tasks) and face-to-face physical interaction with the therapist (for motor tasks) [8,9], and advanced [10,11], using computer-assisted techniques, robotics, or virtual reality (VR) [12][13][14]. Both are based on the use of specific strategies to retrain or alleviate the cognitive [15] and motor [16] alterations in patients with SABI.…”
Section: Introductionmentioning
confidence: 99%